Newly-Diagnosed Diabetes and Sustained Hyperglycemia are Associated with Poorer Outcomes in COVID-19 Inpatients Without Pre-Existing Diabetes - Lin L; Chen Z; Ding T; Liu H; Zhou F; Huang X; Zhang X; Liu W; Zhang BH; Yuan Y; Zhang P; Zhang XJ; et al. (Diabetes, Metabolic Syndrome and Obesity, 2021)
Lijin Lin,1– 4,* Ze Chen,4,5,* Ting Ding,1,2,* Hui Liu,4,6,* Feng Zhou,4,7 Xuewei Huang,3,4 Xingyuan Zhang,4,8 Weifang Liu,4,8 Bing-Hong Zhang,9 Yufeng Yuan,10 Peng Zhang,4,8 Xiao-Jing Zhang,4,8 Zhi-Gang She,3,4 Jingjing Cai,4,11 Wenping Chen,1,2 Hongliang Li2– 4,7 1Department of Endocrinology, Huanggang Central Hospital, Huanggang, People’s Republic of China; 2Huanggang Institute of Translational Medicine, Huanggang, People’s Republic of China; 3Department of Cardiology, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of China; 4Institute of Model Animal of Wuhan University, Wuhan, People’s Republic of China; 5Department of Cardiology, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 6Neonatology of Gastroenterology, Tongren Hospital of Wuhan University & Wuhan Third Hospital, Wuhan, People’s Republic of China; 7Medical Science Research Center, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 8Basic Medical School of Wuhan University, Wuhan, People’s Republic of China; 9Neonatology Department, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of China; 10Department of Hepatobiliary and Pancreatic Surgery, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 11Department of Cardiology, The Third Xiangya Hospital, Central South University, Changsha, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongliang Li; Wenping Chen Email lihl@whu.edu.cn; chenwenping@hgyy.org.cnPurpose: To analyze the impact of hyperglycemia on the clinical outcome of COVID-19 in patients with newly diagnosed diabetes (NDD).Patients and Methods: We performed a retrospective study of 3114 cases of COVID-19 without pre-existing diabetes, 351 of which had NDD, in Hubei Province, China. The Cox regression model was used to calculate the risk of adverse clinical outcomes comparing the NDD vs non-NDD group before and after propensity score-matched (PSM) analysis. Patients with NDD were further divided into a sustained hyperglycemia group, a fluctuating group, and a remitted group based on their blood glucose levels during hospitalization as well as into hypoglycemic agent users and nonusers.Results: Compared to the non-NDD individuals, individuals with NDD had a significantly increased risk of all-cause mortality (adjusted HR after PSM, 2.65; 95% CI, 1.49– 4.72; P = 0.001) and secondary outcomes involving organ damage during the 28-day follow-up period. Subgroup analyses indicated that among individuals with NDD, the individuals with remitted hyperglycemia had the lowest 28-day mortality, whereas those with sustained hyperglycemia had the highest (IRR 24.27; 95% CI, 3.21– 183.36; P < 0.001). Moreover, individuals treated with hypoglycemic agents had significantly lower all-cause mortality than those not treated with hypoglycemic agents (IRR 0.08; 95% CI, 0.01– 0.56; P < 0.001).Conclusion: Our study reinforces the clinical message that NDD is strongly associated with poor outcomes in COVID-19 patients. Furthermore, resolved hyperglycemia in the later phase of the disease and the use of hypoglycemic agents were associated with improved prognosis in patients with NDD.Keywords: COVID-19, newly diagnosed diabetes, hyperglycemia, prognosis, blood glucose